Structure and function of a near fully-activated intermediate GPCR-Gαβγ complex - Maxine Bi; Xudong Wang; Jinan Wang; Jun Xu; Wenkai Sun; Victor Ayo Adediwura; Yinglong Miao; Yifan Cheng; Libin Ye (Nature Communications)
Abstract Unraveling the signaling roles of intermediate complexes is pivotal for G protein-coupled receptor (GPCR) drug development. Despite hundreds of GPCR-Gαβγ structures, these snapshots primarily capture the fully activated complex. Consequently, the functions of intermediate GPCR-G protein complexes remain elusive. Guided by a conformational landscape visualized via 19F quantitative NMR and molecular dynamics (MD) simulations, we determined the structure of an intermediate GPCR-mini-Gαsβγ complex at 2.6 Å using cryo-EM, by blocking its transition to the fully activated complex. Furthermore, we present direct evidence that the complex at this intermediate state initiates a rate-limited nucleotide exchange before transitioning to the fully activated complex. In this state, BODIPY-GDP/GTP based nucleotide exchange assays further indicated the α-helical domain of the Gα is partially open, allowing it to grasp a nucleotide at a non-canonical binding site, distinct from the canonical nucleotide-binding site. These advances bridge a significant gap in our understanding of the complexity of GPCR signaling.